Outcomes of Kidney Transplantation in HIV-Infected Recipients - Stock, Peter G. (2010)
BACKGROUND: The outcomes of kidney transplantation and immunosuppression in people infected with human immunodeficiency virus (HIV) are incompletely understood. METHODS: We undertook a prospective, nonrandomized trial of kidney transplantation in HIV-infected candidates who had CD4+ T-cell counts of at least 200 per cubic millimeter and undetectable plasma HIV type 1 (HIV-1) RNA levels while being treated with a stable antiretroviral regimen. Post-transplantation management was provided in accordance with study protocols that defined prophylaxis against opportunistic infection, indications for biopsy, and acceptable approaches to immunosuppression, management of rejection, and antiretroviral therapy. RESULTS: Between November 2003 and June 2009, a total of 150 patients underwent kidney transplantation; survivors were followed for a median period of 1.7 years. Patient survival rates (±SD) at 1 year and 3 years were 94.6±2.0% and 88.2±3.8%, respectively, and the corresponding mean graft-survival rates were 90.4% and 73.7%. In general, these rates fall somewhere between those reported in the national database for older kidney-transplant recipients (≥65 years) and those reported for all kidney-transplant recipients. A multivariate proportional-hazards analysis showed that the risk of graft loss was increased among patients treated for rejection (hazard ratio, 2.8; 95% confidence interval [CI], 1.2 to 6.6; P = 0.02) and those receiving antithymocyte globulin induction therapy (hazard ratio, 2.5; 95% CI, 1.1 to 5.6; P = 0.03); living-donor transplants were protective (hazard ratio, 0.2; 95% CI, 0.04 to 0.8; P = 0.02). A higher-than-expected rejection rate was observed, with 1-year and 3-year estimates of 31% (95% CI, 24 to 40) and 41% (95% CI, 32 to 52), respectively. HIV infection remained well controlled, with stable CD4+ T-cell counts and few HIV-associated complications. CONCLUSIONS: In this cohort of carefully selected HIV-infected patients, both patient- and graft-survival rates were high at 1 and 3 years, with no increases in complications associated with HIV infection. The unexpectedly high rejection rates are of serious concern and indicate the need for better immunotherapy.